(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Ectopic pregnancy is one of the most common causes of the life-threatening condition. It affects the most important group of the population which contributes to the growth of society. The ease of identification through the clinical presentation and the availability of newer modalities for confirming diagnosis make the clinician duty-bound to save such patients from preventable complications and death. The patient usually presents with the triad of amenorrhea, pain abdomen, and bleeding per vagina. Unfortunately, only half of them present with such symptoms. Patient concerns: Our case series describes different cases of unruptured ectopic pregnancy with unusual presentation. In this, we present 4 cases of ectopic pregnancy who reported to our hospital. The first case was failed medical management of ectopic pregnancy, the second was asymptomatic with a history of previous ectopic pregnancy revealing live unruptured tubal ectopic of 13 weeks, the third was ectopic pregnancy following ovulation induction and the last was multiparous with no identifiable risk factor who came with history of amenorrhea. The above cases were identified using biochemical parameters Bhcg and transvaginal ultrasonography and were subsequently confirmed by laparoscopy and proven on histopathology. Judicious use of ultrasound in an appropriate clinical setting can thus prevent mishaps and enable better management of such conditions. Conclusion: Patients with unusual presentation who are vitally stable may be challenging to an obstetrician for early identification and diagnosis. The line of management in ectopic depends upon the condition of the patient, diagnostic findings, and lab parameters.